2022
DOI: 10.1186/s12302-022-00662-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and analysis of key studies used to restrict substances under REACH

Abstract: Background Understanding how scientific studies are used in regulatory risk assessments is important since it influences the outcome of an assessment, and thus the level of protection of human health and the environment. Within the REACH legislation (Registration, Evaluation, Authorisation and Restriction of Chemicals, EC Nr. 1907/2006) hazard information on clearly defined (eco-)toxicological endpoints are submitted for the registration of substances, and this information is intended for concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…On the one hand, REACH requires chemical companies to disclose more information about the risks that their products pose to the environment and human health; on the other hand, it offers the possibility of registration exemptions for a process that supports new, sustainable innovation for five years. To establish a sustainable chemical industry, other nations have been inspired by the European Union to develop rules along similar lines [141].…”
Section: Policy and Structural Issues Related To Ce And Gc Integratio...mentioning
confidence: 99%
“…On the one hand, REACH requires chemical companies to disclose more information about the risks that their products pose to the environment and human health; on the other hand, it offers the possibility of registration exemptions for a process that supports new, sustainable innovation for five years. To establish a sustainable chemical industry, other nations have been inspired by the European Union to develop rules along similar lines [141].…”
Section: Policy and Structural Issues Related To Ce And Gc Integratio...mentioning
confidence: 99%
“…In terms of reliability, data provided by industry within chemical legislation have been questioned in terms of compliance, quality, and usefulness for risk-reduction measures. A large, systematic evaluation of EU REACH registration dossiers revealed that the chemical industry often failed to comply with the data requirements. Of 1932 dossiers of chemicals produced or imported to the EU in amounts of >1000 tonnes per year, only one dossier complied with the requirements for all end points .…”
Section: Availability and Usefulness Of Chemical Industry Data For Th...mentioning
confidence: 99%
“…This highlights the importance for the Panel to make use of all available reliable and relevant data and not to limit itself to prescribed data formats such as those defined by specific test guidelines or good laboratory practice (GLP), as such a limitation may exclude studies of significance, especially from all geographic areas. Studies from the scientific literature have proven to be valuable in the restriction of chemicals under the EU chemicals regulation, REACH, meaning that these studies were considered of sufficient reliability and relevance . As a model, the new Transparency Regulation in the European Union’s food laws is also expected to open up previously unavailable data for use in other domains of chemical oversight in the EU and beyond.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from the scientific literature have proven to be valuable in the restriction of chemicals under the EU chemicals regulation, REACH, meaning that these studies were considered of sufficient reliability and relevance. 12 As a model, the new Transparency Regulation in the European Union’s food laws is also expected to open up previously unavailable data for use in other domains of chemical oversight in the EU and beyond. Transparency of data and the Panel’s workflow is crucial.…”
Section: Introductionmentioning
confidence: 99%